Pendampingan dan Penerapan AI dalam Proses Desain Grafis untuk Meningkatkan Keterampilan Siswa - Qusyairi, Muhammad; I Putu Sugi Almantara; Yogiswara Dharma Putra; Putu Astya Prayudha (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
The development of Artificial Intelligence (AI) technology has had a significant impact on the learning process, including in Graphic Design subjects at the Vocational High School (SMK) level. This study aims to analyze the effectiveness of utilizing AI as a digital-based learning medium that can improve creativity, technical skills, and design process efficiency in students. The research method used is a systematic literature review by reviewing relevant research from 2021–2025, including studies on the integration of AI in design education, the use of generative AI, its impact on creativity, and the adoption of educational technology in vocational environments. The results of the study indicate that the use of AI such as generative design tools, AI image generation, and adaptive learning platforms significantly improves visual exploration skills, accelerates the ideation process, and helps students understand basic design principles more interactively. However, the study also identified several challenges, such as the potential for design fixation, dependence on technology, issues of work authenticity, and limited teacher competency in operating AI-based devices. Overall, the use of AI in Graphic Design learning at vocational high schools has made a positive contribution to the quality of learning and students' readiness to face the digital-based creative industry. This study found that students' graphic design skills increased by 20.37%, which was carried out using pre-testing and an ethical AI usage policy to ensure that this technology can be utilized optimally and sustainably in education.